Waterproof anticorrosive finish paint and preparation method thereof
By introducing a waterproof and anti-corrosion topcoat with fluorinated phenyl isocyanate through a step-by-step configuration, the problem of insufficient performance of existing anti-corrosion topcoats in harsh environments is solved, achieving high-efficiency waterproof, anti-corrosion and weather-resistant performance, and improving the mechanical properties of the topcoat.
Patent Information
- Application Number
- CN202511619821.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-06
- Publication Date
- 2025-12-16
AI Technical Summary
Existing anti-corrosion topcoats are difficult to simultaneously possess excellent waterproof, anti-corrosion, weather-resistant, and mechanical properties under harsh environments, and are prone to gelling or failure during storage.
The waterproof and anti-corrosion topcoat is formulated in stages, consisting of a first component and a second component, which respectively include hydroxyl acrylic resin and fluorinated phenyl isocyanate. This avoids premature reaction and introduces fluorinated methyl and benzene ring structures through fluorinated phenyl isocyanate, thereby improving anti-corrosion performance and mechanical properties.
It significantly extends the corrosion resistance and weather resistance of the topcoat, improves its waterproof and stain-resistant properties, enhances the hardness and impact resistance of the paint film, and ensures stable coating quality.
Smart Images

Figure CN121136587A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of coatings, in particular to a waterproof and anticorrosive finish paint and a preparation method thereof. BACKGROUND
[0002] In the fields of transportation tools, marine engineering, etc., the substrate is easily subjected to chemical corrosion or electrochemical corrosion when exposed to complex environments such as atmosphere, seawater, acid and alkali medium for a long time, resulting in substrate failure and structure damage, which not only causes huge economic losses, but also may cause safety accidents. Therefore, developing an anticorrosive finish paint with excellent waterproof and anticorrosive properties while taking into account film-forming property, adhesion and weather resistance has become one of the core demands in the field of coatings.
[0003] Hydroxy acrylic resin has various advantages and is widely used in traditional anticorrosive finish paint systems. For example, a water-based fluorocarbon modified acrylic polyurethane finish paint and a preparation method thereof are disclosed in Chinese Patent Application No. CN108165151A. The finish paint is composed of A component and B component. The A component is composed of water-based hydroxy acrylic dispersion, water-based fluorocarbon resin, dispersant, titanium white, catalyst, substrate wetting agent, defoaming agent, rheological aid and deionized water; the B component is composed of HDI type isocyanate curing agent, anhydrous diluent and dehydrating agent. The finish paint has superior light and color retention, corrosion resistance, chemical resistance, weather resistance and stain resistance.
[0004] However, as the application environment becomes more demanding, more anticorrosive finish paints with hydroxy acrylic resin as the film-forming resin need to be developed. SUMMARY
[0005] In view of the deficiencies of the prior art, the present application provides a waterproof and anticorrosive finish paint and a preparation method thereof. The first component is obtained by adding solvents, dispersants, fillers and pigments, resins, defoaming agents and leveling agents step by step, fully mixing and sieving. The second component is prepared by mixing fluorine-containing phenyl isocyanate and co-curing agent under the protection of protective gas, adding solvents and catalysts, mixing uniformly under controlled temperature, and further sieving. Finally, the two components are mixed and stirred in proportion and left to mature to obtain the waterproof and anticorrosive finish paint. The component configuration of the present application is reasonable, the preparation process is controllable, the obtained waterproof and anticorrosive finish paint is stable in quality and has excellent anticorrosive performance and related mechanical properties, and can be widely applied to the surface of substrates requiring efficient anticorrosive protection.
[0006] To achieve the above-mentioned purposes, the present application adopts the following technical solutions:
[0007] The waterproof anticorrosive finish paint comprises a first component and a second component; the first component comprises a hydroxyl acrylic resin, a filler, a pigment, a first solvent, a dispersant, a defoaming agent and a leveling agent; the second component comprises a fluorine-containing phenyl isocyanate, a co-curing agent, a second solvent and a catalyst; the fluorine-containing phenyl isocyanate is any one of 4-(trifluoromethyl)phenyl isocyanate, 3,5-bis(trifluoromethyl)phenyl isocyanate and 4-chloro-3-trifluoromethylphenyl isocyanate.
[0008] In the waterproof anticorrosive finish paint provided by the application, the first component and the second component are stored separately, which can avoid the reaction between -NCO in the fluorine-containing phenyl isocyanate and -OH in the hydroxyl acrylic resin in advance, and fundamentally eliminate the problems such as gelation and invalidation of the paint during storage. The use of the fluorine-containing phenyl isocyanate can introduce a large number of fluorine-containing methyl groups and benzene ring structures into the prepared waterproof anticorrosive finish paint. The C-F bond in the fluorine-containing methyl group has a very high bond energy, so it is difficult to be attacked by chemical reagents or free radicals and difficult to be damaged by ultraviolet light, and thus the molecular chain in which the fluorine-containing methyl group is located is not prone to breakage or degradation, and can resist the erosion of acid mist, salt mist, organic solvents and other complex environments such as atmosphere, seawater, acid and alkali medium, thereby significantly prolonging the anticorrosive service life of the finish paint, improving the weather resistance and ultraviolet resistance of the finish paint. In addition, the introduction of fluorine atoms has a shielding and protective effect on other structures in the finish paint, thereby reducing the surface free energy of the prepared finish paint, making it difficult for water, oil stains, dust and the like to adhere, and significantly improving the waterproof and stain resistance of the finish paint. In addition, the synchronous introduction of the rigid benzene ring structure increases the rigidity of the resin molecular chain, reduces the chain segment movement ability, and increases the glass transition temperature and hardness of the coating. The introduction of the rigid benzene ring structure also reduces the deformation of the coating when subjected to stress, and improves the mechanical properties such as wear resistance and impact resistance of the paint film.
[0009] In an available embodiment, the mass ratio of the first component to the second component is (4-10):1; in the first component, the mass ratio of the hydroxyl acrylic resin, the filler, the pigment, the first solvent, the dispersant, the defoaming agent and the leveling agent is (30-50):(10-20):(15-20):(20-30):(0.5-2):(0.2-2):(0.3-1); in the second component, the mass ratio of the fluorine-containing phenyl isocyanate, the co-curing agent, the second solvent and the catalyst is (40-60):(20-30):(15-30):(1-5).
[0010] In the waterproof anticorrosive finish paint provided by the application, the mass ratio of the components in the first component and the second component is controlled, so that the finish paint coating is completely crosslinked and has balanced performance, and the problems such as sagging caused by too much solvent or too high viscosity that cannot be constructed caused by too little solvent are avoided.
[0011] In an embodiment, the dispersant includes any one or more of BYK-163, BYK-110, and EFKA-4046; the defoamer includes any one or more of BYK-035, BYK-054, and EFKA-2526; and the leveling agent includes any one or more of BYK-306, BYK-358N, and EFKA-3030.
[0012] In an embodiment, the hydroxyl value of the hydroxyl acrylic resin is 50-120 mgKOH / g.
[0013] In the waterproof anticorrosive topcoat provided by the present application, the hydroxyl value range represents the hydroxyl content range of the hydroxyl acrylic resin; controlling the hydroxyl content in this range can avoid the problems of soft coating, poor scratch resistance caused by too low hydroxyl value, or brittle coating, easy cracking caused by too high hydroxyl value; and this hydroxyl content matches the reactivity of -NCO in the second component, ensuring that the topcoat film forming speed meets the construction requirements.
[0014] In an embodiment, the filler includes any one or more of talc, barite, kaolin, mica powder, and calcium carbonate; and the pigment includes any one of titanium dioxide, carbon black, and iron red.
[0015] In an embodiment, the first solvent includes any one or more of n-butyl acetate, n-pentyl acetate, propylene glycol methyl ether acetate, and dipropylene glycol methyl ether acetate.
[0016] In the waterproof anticorrosive topcoat provided by the present application, the solvent used in the first component can sufficiently dissolve the hydroxyl acrylic resin, avoiding delamination caused by resin precipitation; and the volatilization speed is moderate, which can prevent defects such as orange peel, pinholes, and sagging in the coating.
[0017] In an embodiment, the co-curing agent includes any one or more of dicyclohexyl methane diisocyanate, diphenyl methane diisocyanate, and hexamethylene diisocyanate trimer.
[0018] In the waterproof anticorrosive topcoat provided by the present application, the use of the co-curing agent can cooperate with the fluorine-containing phenyl isocyanate as the main curing agent, adapt to different construction environments, and improve the properties such as yellowing resistance and crosslinking degree.
[0019] In an embodiment, the second solvent includes any one or more of n-butyl acetate, t-butyl acetate, and dipropylene glycol dimethyl ether; and the catalyst includes any one or more of dibutyl tin dilaurate, dibutyl tin dioctanoate, and bismuth isooctoate.
[0020] The waterproof anticorrosive finish paint provided in the application, the solvent used by the second component can maintain the stability of the fluorine-containing phenyl isocyanate as the main curing agent, the co-curing agent and the catalyst in the second component, and improve the compatibility after mixing with the first component.
[0021] A preparation method of a waterproof anticorrosive finish paint, comprising the following steps:
[0022] 50% of the first solvent is added into the first stirring tank, the dispersant is added under the rotation speed of 500-800 rpm, and stirring is performed for 5-10 min; then the filler and the pigment are sequentially added, and stirring is continuously performed for 10-15 min to form a uniform slurry;
[0023] The stirring rotation speed in the first stirring tank is increased to 1200-1500 rpm, and stirring is continuously performed for 20-30 min;
[0024] Then the stirring rotation speed is decreased to 600-800 rpm, the hydroxyl acrylic resin is added, and stirring is performed for 15-20 min; the remaining 50% of the first solvent is added, and stirring is continuously performed for 10-15 min; finally, the defoaming agent and the leveling agent are sequentially added, and stirring is continuously performed for 20-30 min to obtain the first component pre-product; the first component pre-product is sieved to obtain the first component;
[0025] The fluorine-containing phenyl isocyanate and the co-curing agent are added into the second stirring tank protected by the protective gas, stirring is performed at the rotation speed of 500-600 rpm for 10-15 min to obtain the mixed curing agent;
[0026] The rotation speed is kept unchanged, the second solvent is added into the mixed curing agent, and stirring is performed for 10-15 min; then the catalyst is added, and stirring is continuously performed for 20-30 min under the condition of controlling the temperature in the second stirring tank to obtain the second component pre-product; the second component pre-product is sieved to obtain the second component;
[0027] Finally, the first component and the second component are added into the stirring container, stirring is performed at the rotation speed of 400-600 rpm for 5-10 min, and then standing and curing is performed for 10-20 min to obtain the waterproof anticorrosive finish paint.
[0028] In an available embodiment, the sieve used for sieving the first component pre-product is a 150-mesh sieve; and the sieve used for sieving the second component pre-product is a 200-mesh sieve. In this way, it can be ensured that there is no large-particle impurity in the prepared first component and second component, so that the finish paint coating is smooth and flat, and has no pinholes or protrusions, and the anticorrosion stability is stable.
[0029] In an available embodiment, the protective gas includes any one or more of nitrogen and argon.
[0030] For a feasible embodiment, the temperature in the second stirring tank is controlled at 25-40℃ by means of cooling water through the jacket. In this way, the solidification agent gel caused by local overheating can be avoided, and the quality of the second component can be ensured to be stable; and the jacket cooling does not have direct contact, so that the cooling water can be prevented from mixing with the solidification agent to cause the -NCO to be ineffective.
[0031] Beneficial technical effects:
[0032] In the prepared waterproof anticorrosive topcoat, a large number of fluorine-containing methyl groups and benzene ring structures are introduced through the reaction of the hydroxy acrylate resin and the fluorine-containing phenyl isocyanate. The C-F bond energy in the fluorine-containing methyl group is very high, so it is difficult to be attacked by chemical reagents or free radicals, and it is also difficult to be damaged by ultraviolet light, and thus the molecular chain in which it is located is not easy to break or degrade, and it can resist the corrosion of acid mist, salt mist and organic solvents existing in different application environments such as transportation tools and marine engineering, significantly prolonging the anticorrosive service life, weather resistance and ultraviolet resistance of the topcoat. In addition, the introduction of fluorine atoms has a shielding and protective effect on other structures in the topcoat, thereby reducing the surface free energy of the prepared topcoat, making it difficult for water, oil stains and dust to adhere, and significantly improving the waterproof and stain resistance of the topcoat. In addition, the synchronous introduction of the rigid benzene ring structure increases the rigidity of the resin molecular chain, reduces the chain segment movement ability, increases the glass transition temperature of the coating, and improves the hardness. The introduction of the rigid benzene ring structure also reduces the deformation of the coating when under stress, and improves the mechanical properties such as wear resistance and impact resistance of the paint film. BRIEF DESCRIPTION OF DRAWINGS
[0033] Figure 1 is a physical diagram of the waterproof anticorrosive topcoat prepared in Example 1.
[0034] Figure 2 is a flowchart of the preparation method of the waterproof anticorrosive topcoat. DETAILED DESCRIPTION
[0035] In order to make the content described in the present application more convenient to understand, the technical solutions described in the present application will be further described in combination with specific embodiments, but the present application is not limited thereto. Any equivalent transformation or simple substitution made according to the essential content of the present application shall be within the protection scope of the present application.
[0036] The singular forms "is", "or", "a", "any" and "the" used in the present application are intended to include the plural forms, unless the context clearly indicates otherwise.
[0037] The preparation method of the waterproof anticorrosive topcoat provided by the present application will be described in detail below in combination with different embodiments.
[0038] Example 1
[0039] AsFigure 2 As shown in the figure, a preparation method of a waterproof and anticorrosive finish paint comprises the following steps:
[0040] 1. Add 50% n-butyl acetate into a first stirring tank, add BYK-163 at a rotating speed of 600 rpm, and stir for 8 min; then add talcum powder and titanium dioxide in sequence, and continuously stir for 12 min to form a uniform slurry;
[0041] 2. Increase the stirring rotating speed in the first stirring tank to 1300 rpm, and continuously stir for 25 min;
[0042] 3. Then, reduce the stirring rotating speed to 700 rpm, add a hydroxyl acrylic resin (with a hydroxyl value of 50 mgKOH / g), and stir for 18 min; then add the remaining 50% n-butyl acetate, and continuously stir for 12 min; finally, add BYK-035 and BYK-306 in sequence, and stir for 25 min to obtain a first component pre-product; pass the first component pre-product through a 150-mesh sieve to obtain the first component;
[0043] In the above steps 1-3, the mass ratio of the hydroxyl acrylic resin (with a hydroxyl value of 50 mgKOH / g), talcum powder, titanium dioxide, n-butyl acetate, BYK-163, BYK-035 and BYK-306 is 40:15:18:24:1:1.7:0.3;
[0044] 4. Add 4-(trifluoromethyl)phenyl isocyanate and dicyclohexylmethane diisocyanate into a second stirring tank under nitrogen protection, and stir at a rotating speed of 550 rpm for 12 min to obtain a mixed curing agent;
[0045] 5. Keep the rotating speed unchanged, add n-butyl acetate into the mixed curing agent, and stir for 13 min; then add dibutyltin dilaurate drop by drop, and continuously stir for 25 min under the condition that the temperature in the second stirring tank is controlled at 30°C to obtain a second component pre-product; pass the second component pre-product through a 200-mesh sieve to obtain the second component;
[0046] In the above steps 4-5, the mass ratio of 4-(trifluoromethyl)phenyl isocyanate, dicyclohexylmethane diisocyanate, n-butyl acetate and dibutyltin dilaurate is 50:25:22:3;
[0047] 6. Finally, add the first component and the second component into a stirring container at a mass ratio of 6:1, and stir at a rotating speed of 500 rpm for 8 min; then stand for 15 min to obtain the waterproof and anticorrosive finish paint, and the actual picture is as shown in the figure. Figure 1
[0048] Example 2
[0049] As Figure 2 As shown, a method for preparing a waterproof and anti-corrosion topcoat includes the following steps:
[0050] 1. Add 50% n-amyl acetate to the first mixing tank, add BYK-110 at 550 rpm and stir for 6 minutes; then add barite powder and carbon black in sequence and continue stirring for 11 minutes to form a uniform slurry.
[0051] 2. Increase the stirring speed in the first mixing tank to 1200 rpm and maintain it for 28 minutes;
[0052] 3. Then reduce the stirring speed to 650 rpm, add hydroxyl acrylic resin (hydroxyl value 80 mg KOH / g), and stir for 16 min; then add the remaining 50% of n-amyl acetate, and continue stirring for 11 min; finally, add BYK-054 and BYK-358N in sequence, and stir for 22 min to obtain the first component pre-finished product; pass the first component pre-finished product through a 150-mesh sieve to obtain the first component;
[0053] In steps 1 to 3 above, the mass ratio of hydroxyl acrylic resin (hydroxyl value 80 mg KOH / g), barite powder, carbon black, n-amyl acetate, BYK-110, BYK-054, and BYK-358N is 35:18:20:25:0.7:0.4:0.9.
[0054] 4. Add 3,5-bis(trifluoromethyl)phenyl isocyanate and diphenylmethane diisocyanate to the second mixing tank under argon protection, and stir at 520 rpm for 14 min to obtain a mixed curing agent;
[0055] 5. Keeping the rotation speed constant, add tert-butyl acetate to the mixed curing agent and stir for 12 minutes; then add dibutyltin dioctanoate dropwise and continue stirring for 28 minutes while controlling the temperature in the second mixing tank at 28°C to obtain the second component pre-finished product; pass the second component pre-finished product through a 200-mesh sieve to obtain the second component;
[0056] In steps 4-5 above, the mass ratio of 3,5-bis(trifluoromethyl)phenyl isocyanate, diphenylmethane diisocyanate, tert-butyl acetate, and dibutyltin dioctanoate is 45:30:22:3.
[0057] 6. Finally, add the first component and the second component into the mixing container at a mass ratio of 4:1, stir at 450 rpm for 7 minutes, and then let stand for 12 minutes to mature, thus obtaining the waterproof and anti-corrosion topcoat.
[0058] Example 3
[0059] like Figure 2 As shown, a method for preparing a waterproof and anti-corrosion topcoat includes the following steps:
[0060] 1. Add 50% propylene glycol methyl ether acetate to the first mixing tank, add EFKA-4046 at 750 rpm and stir for 9 min; then add kaolin and iron oxide red in sequence and continue stirring for 14 min to form a uniform slurry;
[0061] 2. Increase the stirring speed in the first mixing tank to 1400 rpm and maintain it for 22 minutes;
[0062] 3. Then reduce the stirring speed to 750 rpm, add hydroxyl acrylic resin (hydroxyl value 100 mg KOH / g), and stir for 19 min; then add the remaining 50% of propylene glycol methyl ether acetate, and continue stirring for 14 min; finally, add EFKA-2526 and EFKA-3030 in sequence, and stir for another 28 min to obtain the first component pre-finished product; pass the first component pre-finished product through a 150-mesh sieve to obtain the first component;
[0063] In steps 1 to 3 above, the mass ratio of hydroxyl acrylic resin (hydroxyl value 100 mg KOH / g), kaolin, iron oxide red, propylene glycol methyl ether acetate, EFKA-4046, EFKA-2526, and EFKA-3030 is 45:12:16:25:0.6:0.5:0.9.
[0064] 4. Add 4-chloro-3-trifluoromethyl phenyl isocyanate and hexamethylene diisocyanate trimer to the second mixing tank under nitrogen protection, and stir at 580 rpm for 11 min to obtain a mixed curing agent;
[0065] 5. Keeping the rotation speed constant, add dipropylene glycol dimethyl ether to the mixed curing agent and stir for 14 minutes; then add bismuth isooctanoate dropwise and continue stirring for 22 minutes while controlling the temperature in the second mixing tank at 35°C to obtain the second component pre-finished product; pass the second component pre-finished product through a 200-mesh sieve to obtain the second component;
[0066] In steps 4-5 above, the mass ratio of 4-chloro-3-trifluoromethyl isocyanate, hexamethylene diisocyanate trimer, dipropylene glycol dimethyl ether, and bismuth isooctanoate is 55:22:20:3.
[0067] 6. Finally, add the first component and the second component into the mixing container at a mass ratio of 8:1, stir at 550 rpm for 9 minutes, and then let stand for 18 minutes to mature, thus obtaining the waterproof and anti-corrosion topcoat.
[0068] Example 4
[0069] like Figure 2 As shown, a method for preparing a waterproof and anti-corrosion topcoat includes the following steps:
[0070] 1. Add 50% dipropylene glycol methyl ether acetate to the first mixing tank, add BYK-163 at 500 rpm and stir for 5 minutes; then add mica powder and titanium dioxide in sequence and continue stirring for 10 minutes to form a uniform slurry.
[0071] 2. Increase the stirring speed in the first mixing tank to 1500 rpm and maintain it for 20 minutes;
[0072] 3. Then reduce the stirring speed to 600 rpm, add hydroxyl acrylic resin (hydroxyl value 60 mg KOH / g), and stir for 15 min; then add the remaining 50% of dipropylene glycol methyl ether acetate, and continue stirring for 10 min; finally, add BYK-035 and BYK-306 in sequence, and stir for another 20 min to obtain the first component pre-finished product; pass the first component pre-finished product through a 150-mesh sieve to obtain the first component;
[0073] In steps 1 to 3 above, the mass ratio of hydroxyl acrylic resin (hydroxyl value 60 mg KOH / g), mica powder, titanium dioxide, dipropylene glycol methyl ether acetate, BYK-163, BYK-035 and BYK-306 is 30:20:19:29:0.5:0.8:0.7.
[0074] 4. Add 4-(trifluoromethyl)phenyl isocyanate and dicyclohexylmethane diisocyanate to the second mixing tank under argon protection, and stir at 500 rpm for 10 min to obtain a mixed curing agent;
[0075] 5. Keeping the rotation speed constant, add n-butyl acetate to the mixed curing agent and stir for 10 minutes; then add dibutyltin dilaurate dropwise and continue stirring for 20 minutes while controlling the temperature in the second mixing tank at 25°C to obtain the second component pre-finished product; pass the second component pre-finished product through a 200-mesh sieve to obtain the second component;
[0076] In steps 4-5 above, the mass ratio of 4-(trifluoromethyl)phenyl isocyanate, dicyclohexylmethane diisocyanate, n-butyl acetate, and dibutyltin dilaurate is 40:30:25:5.
[0077] 6. Finally, add the first component and the second component in a mass ratio of 10:1 into the mixing container, stir at 400 rpm for 5 minutes, and then let stand for 10 minutes to mature, thus obtaining the waterproof and anti-corrosion topcoat.
[0078] Example 5
[0079] like Figure 2 As shown, a method for preparing a waterproof and anti-corrosion topcoat includes the following steps:
[0080] 1. Add 50% of n-butyl acetate into the first stirring tank, add BYK-110 at 800 rpm, and stir for 10 min; then add calcium carbonate and carbon black in sequence, continue to stir for 15 min to form a uniform slurry;
[0081] 2. Increase the stirring speed of the first stirring tank to 1350 rpm for 30 min;
[0082] 3. Then reduce the stirring speed to 800 rpm, add hydroxy acrylic resin (hydroxyl value is 90 mgKOH / g), and stir for 20 min; then add the remaining 50% of n-butyl acetate, continue to stir for 15 min, and finally add BYK-054, BYK-358N in sequence, and stir for 30 min to obtain a first component pre-product; pass the first component pre-product through a 150 mesh sieve to obtain the first component;
[0083] In steps 1-3 above, the mass ratio of hydroxy acrylic resin (hydroxyl value is 90 mgKOH / g), calcium carbonate, carbon black, n-butyl acetate, BYK-110, BYK-054 and BYK-358N is 50:10:15:22:2:0.2:0.8;
[0084] 4. Add 3,5-bis(trifluoromethyl)phenyl isocyanate and diphenylmethane diisocyanate into the second stirring tank under nitrogen protection, stir at 600 rpm for 15 min to obtain a mixed curing agent;
[0085] 5. Keep the stirring speed unchanged, add t-butyl acetate into the mixed curing agent, stir for 15 min; then add dibutyltin dioctoate drop by drop, and continue to stir for 30 min under the condition of controlling the temperature in the second stirring tank to 40℃ to obtain a second component pre-product; pass the second component pre-product through a 200 mesh sieve to obtain the second component;
[0086] In steps 4-5 above, the mass ratio of 3,5-bis(trifluoromethyl)phenyl isocyanate, diphenylmethane diisocyanate, t-butyl acetate and dibutyltin dioctoate is 60:20:15:5;
[0087] 6. Finally, add the first component and the second component with a mass ratio of 7:1 into a stirring container, stir at 600 rpm for 10 min, and then stand for 20 min to obtain the waterproof and anticorrosive finish.
[0088] Example 6
[0089] As Figure 2 shown, a preparation method of a waterproof and anticorrosive finish, comprising the following steps:
[0090] 1. Add 50% propylene glycol methyl ether acetate into the first stirring tank, add EFKA-4046 at 650 rpm, and stir for 7 min; then add talcum powder and iron red in sequence, and continuously stir for 13 min to form a uniform slurry;
[0091] 2. Increase the stirring speed of the first stirring tank to 1250 rpm, and continuously stir for 26 min;
[0092] 3. Then reduce the stirring speed to 720 rpm, add hydroxy acrylate resin (hydroxyl value is 120 mgKOH / g), and stir for 17 min; then add the remaining 50% propylene glycol methyl ether acetate, and continuously stir for 13 min; finally add EFKA-2526 and EFKA-3030 in sequence, and stir for 26 min to obtain a first component pre-product; pass the first component pre-product through a 150-mesh sieve to obtain the first component;
[0093] In steps 1-3 above, the mass ratio of the hydroxy acrylate resin (hydroxyl value is 120 mgKOH / g), talcum powder, iron red, propylene glycol methyl ether acetate, EFKA-4046, EFKA-2526, and EFKA-3030 is 42:16:17:23:1.2:0.3:0.5;
[0094] 4. Add 4-chloro-3-trifluoromethyl phenyl isocyanate and hexamethylene diisocyanate trimer into the second stirring tank under argon protection, and stir at 560 rpm for 13 min to obtain a mixed curing agent;
[0095] 5. Keep the stirring speed unchanged, add dipropylene glycol dimethyl ether into the mixed curing agent, and stir for 11 min; then add bismuth isooctoate drop by drop, and continuously stir for 24 min under the condition that the temperature in the second stirring tank is controlled at 32℃ to obtain a second component pre-product; pass the second component pre-product through a 200-mesh sieve to obtain the second component;
[0096] In steps 4-5 above, the mass ratio of 4-chloro-3-trifluoromethyl phenyl isocyanate, hexamethylene diisocyanate trimer, dipropylene glycol dimethyl ether, and bismuth isooctoate is 52:26:18:4;
[0097] 6. Finally, add the first component and the second component in a mass ratio of 5:1 into a stirring container, and stir at 480 rpm for 6 min, and then stand for 16 min to obtain the waterproof and anticorrosive finish.
[0098] Comparative Example 1
[0099] A preparation method of a waterproof and anticorrosive finish, comprising the following steps:
[0100] 1. Add 50% n-butyl acetate into the first stirring tank, add BYK-163 at a rotation speed of 600 rpm, and stir for 8 min; then add talcum powder and titanium dioxide in sequence, and continuously stir for 12 min to form a uniform slurry;
[0101] 2. Increase the stirring rotation speed in the first stirring tank to 1300 rpm, and continuously stir for 25 min;
[0102] 3. Then, reduce the stirring rotation speed to 700 rpm, add a hydroxyl acrylic resin (hydroxyl value is 50 mgKOH / g), and stir for 18 min; then add the remaining 50% n-butyl acetate, and continuously stir for 12 min; finally, add BYK-035 and BYK-306 in sequence, and stir for 25 min to obtain a first component pre-product; pass the first component pre-product through a 150-mesh sieve to obtain the first component;
[0103] In the above steps 1-3, the mass ratio of the hydroxyl acrylic resin (hydroxyl value is 50 mgKOH / g), talcum powder, titanium dioxide, n-butyl acetate, BYK-163, BYK-035, and BYK-306 is 40:15:18:24:1:1.7:0.3;
[0104] 4. Add dicyclohexylmethane diisocyanate into the second stirring tank under nitrogen protection, and stir at a rotation speed of 550 rpm for 12 min to obtain a mixed curing agent;
[0105] 5. Keep the rotation speed unchanged, add n-butyl acetate into the mixed curing agent, and stir for 13 min; then add dibutyltin dilaurate drop by drop, and continuously stir for 25 min under the condition that the temperature in the second stirring tank is controlled at 30°C to obtain a second component pre-product; pass the second component pre-product through a 200-mesh sieve to obtain the second component;
[0106] In the above steps 4-5, the mass ratio of dicyclohexylmethane diisocyanate, n-butyl acetate, and dibutyltin dilaurate is 75:22:3;
[0107] 6. Finally, add the first component and the second component in a mass ratio of 6:1 into a stirring container, and stir at a rotation speed of 500 rpm for 8 min; then, stand for 15 min to obtain the waterproof and anticorrosive finish paint.
[0108] Comparative Example 2
[0109] A preparation method of a waterproof and anticorrosive finish paint, comprising the following steps:
[0110] 1. Add 50% propylene glycol methyl ether acetate into the first stirring tank, add EFKA-4046 at a rotation speed of 750 rpm, and stir for 9 min; then add kaolin and iron red in sequence, and continuously stir for 14 min to form a uniform slurry;
[0111] 2. The stirring speed in the first stirring tank was increased to 1400 rpm for 22 min;
[0112] 3. Then the stirring speed was decreased to 750 rpm, and the hydroxy acrylate resin (hydroxyl value 100 mgKOH / g) was added, and stirred for 19 min; the remaining 50% of propylene glycol methyl ether acetate was added, and stirred for 14 min; finally, the EFKA-2526, EFKA-3030 were added in sequence, and stirred for 28 min, to obtain a first component pre-product; the first component pre-product was passed through a 150-mesh sieve to obtain the first component;
[0113] In the above steps 1-3, the mass ratio of the hydroxy acrylate resin (hydroxyl value 100 mgKOH / g), kaolin, iron red, propylene glycol methyl ether acetate, EFKA-4046, EFKA-2526 and EFKA-3030 was 45:12:16:25:0.6:0.5:0.9;
[0114] 4. Into the second stirring tank under nitrogen protection, hexyl isocyanate and hexamethylene diisocyanate trimer were added, and stirred at a speed of 580 rpm for 11 min to obtain a mixed curing agent;
[0115] 5. The stirring speed was kept unchanged, and dipropylene glycol dimethyl ether was added to the mixed curing agent, and stirred for 14 min; then bismuth isooctoate was added dropwise, and continuously stirred for 22 min under the condition that the temperature in the second stirring tank was controlled at 35°C, to obtain a second component pre-product; the second component pre-product was passed through a 200-mesh sieve to obtain the second component;
[0116] In the above steps 4-5, the mass ratio of hexyl isocyanate, hexamethylene diisocyanate trimer, dipropylene glycol dimethyl ether and bismuth isooctoate was 55:22:20:3;
[0117] 6. Finally, the first component and the second component were added to the stirring container in a mass ratio of 8:1, and stirred at a speed of 550 rpm for 9 min, and then stood for 18 min to mature, to obtain the waterproof and anticorrosive finish.
[0118] The waterproof and anticorrosive finish prepared in Examples 1-6 and Comparative Examples 1-2 was tested for mechanical properties and waterproof and anticorrosive properties. The test results are shown in Table 1.
[0119] Table 1 Test results of the waterproof and anticorrosive finish prepared in Examples 1-6 and Comparative Examples 1-2
[0120]
[0121] As shown in Table 1, the mechanical properties and anticorrosive properties of Examples 1-6 are overall better than those of Comparative Examples 1-2.
[0122] The main reason is that the waterproof anticorrosive topcoat prepared in Examples 1-6 introduces a large number of fluorine-containing methyl groups and benzene ring structures in the prepared waterproof anticorrosive topcoat through the reaction of hydroxy acrylic resin with fluorine-containing phenyl isocyanate. The C-F bond in the fluorine-containing methyl group has a very high bond energy, so it is difficult to be attacked by chemical reagents or free radicals, and it is also difficult to be damaged by ultraviolet light, and thus the molecular chain in which it is located is not easy to break or degrade, and it can resist the erosion of acid mist, salt mist, organic solvents, etc. in complex environments such as atmosphere, seawater, acid and alkali medium, significantly prolonging the anticorrosion life, weather resistance and ultraviolet resistance of the topcoat. In addition, the introduction of fluorine atoms has a shielding and protective effect on other structures in the topcoat, thereby reducing the surface free energy of the prepared topcoat, making it difficult for water, oil stains, dust, etc. to adhere, and significantly improving the waterproof and stain resistance of the topcoat. In addition, the synchronous introduction of benzene ring, a rigid structure, increases the rigidity of the resin molecular chain, reduces the chain segment movement ability, and increases the glass transition temperature and hardness of the coating. The introduction of rigid benzene ring structure can also reduce the deformation of the coating under stress, and improve the mechanical properties such as wear resistance and impact resistance of the paint film.
[0123] In contrast, in Comparative Example 1, no fluorine-containing phenyl isocyanate was added in the second component, so no fluorine-containing methyl group and benzene ring were introduced in the prepared waterproof anticorrosive topcoat. Based on the above principles, the mechanical properties and waterproof and anticorrosive properties of the waterproof anticorrosive topcoat obtained in Comparative Example 1 are the worst.
[0124] In Comparative Example 2, only fluorine-containing isocyanate was added, which does not contain a benzene ring, so it is not possible to introduce a benzene ring in the prepared waterproof anticorrosive topcoat. Based on the above principles, the mechanical properties of the waterproof anticorrosive topcoat obtained in Comparative Example 2 are poor, and the waterproof and anticorrosive properties are relatively good.
[0125] The above results show and describe the basic principles and main features of the present application and the advantages of the present application.
[0126] Those skilled in the art should understand that the present application is not limited by the above examples, and the above examples and descriptions in the specification are only to illustrate the principles of the present application. Without departing from the spirit and scope of the present application, various changes and improvements can be made to the present application, and these changes and improvements all fall within the scope of the claimed present application. The scope of protection claimed by the present application is defined by the equivalents of the appended claims.
Claims
1. A water and rot proof finish, characterized in that, The application relates to a two-component polyurethane coating material, which comprises: a first component and a second component; the first component comprises a hydroxyl acrylic resin, a filler, a pigment, a first solvent, a dispersant, an antifoaming agent and a leveling agent; the second component comprises a fluorine-containing phenyl isocyanate, a co-curing agent, a second solvent and a catalyst; the fluorine-containing phenyl isocyanate is any one of 4-(trifluoromethyl)phenyl isocyanate, 3,5-bis(trifluoromethyl)phenyl isocyanate and 4-chloro-3-trifluoromethylphenyl isocyanate. The mass ratio of the first component and the second component is (4-10):1; in the first component, the mass ratio of the hydroxyl acrylic resin, the filler, the pigment, the first solvent, the dispersant, the antifoaming agent and the leveling agent is (30-50):(10-20):(15-20):(20-30):(0.5-2):(0.2-2):(0.3-1); in the second component, the mass ratio of the fluorine-containing phenyl isocyanate, the co-curing agent, the second solvent and the catalyst is (40-60):(20-30):(15-30):(1-5).
2. A water and rot resistant finish according to claim 1, characterised in that, The hydroxyl value of the hydroxyl acrylic resin is 50-120 mgKOH / g.
3. A water and rot resistant finish according to claim 1, wherein The filler comprises any one or more of talcum powder, barite powder, kaolin, mica powder and calcium carbonate; the pigment comprises any one of titanium white powder, carbon black and iron red.
4. A water and rot resistant finish according to claim 2, characterised in that, The first solvent comprises any one or more of n-butyl acetate, n-pentyl acetate, propylene glycol methyl ether acetate and dipropylene glycol methyl ether acetate.
5. A water and rot resistant finish according to claim 2, wherein The co-curing agent comprises any one or more of dicyclohexyl methane diisocyanate, diphenyl methane diisocyanate and hexamethylene diisocyanate trimer.
6. A water and rot resistant finish according to claim 2, wherein The second solvent comprises any one or more of n-butyl acetate, t-butyl acetate and dipropylene glycol dimethyl ether; and the catalyst comprises any one or more of dibutyl tin dilaurate, dibutyl tin dioctate and bismuth isooctoate.
7. A water and rot resistant finish according to claim 2, wherein The application further discloses a preparation method of the two-component polyurethane coating material.
8. The process for the production of a water and rot proof finish according to any one of claims 1 to 7, characterized in that, 50% of the first solvent is added into a first stirring tank, a dispersant is added under the rotation speed of 500-800 rpm, and stirring is conducted for 5-10 min; then the filler and the pigment are sequentially added, and stirring is continuously conducted for 10-15 min to form a slurry; The stirring rotation speed in the first stirring tank is increased to 1200-1500 rpm, and stirring is continuously conducted for 20-30 min; Then the stirring rotation speed is reduced to 600-800 rpm, the hydroxyl acrylic resin is added, and stirring is conducted for 15-20 min; the remaining 50% of the first solvent is added, and stirring is continuously conducted for 10-15 min; finally the antifoaming agent and the leveling agent are sequentially added, and stirring is conducted for 20-30 min to obtain a first component pre-product; The first component pre-product is sieved to obtain the first component; The fluorine-containing phenyl isocyanate and the co-curing agent are added into a second stirring tank protected by a protective gas, stirring is conducted under the rotation speed of 500-600 rpm for 10-15 min to obtain a mixed curing agent; The second solvent is added into the mixed curing agent under the same rotation speed, and stirring is conducted for 10-15 min; then the catalyst is added, and stirring is continuously conducted for 20-30 min under heat preservation to obtain a second component pre-product; The second component pre-product is sieved to obtain the second component. Finally, the first component and the second component are added into the stirring container, stirred at 400-600 rpm for 5-10 min, and then left to stand and mature for 10-20 min, to obtain the waterproof anticorrosive finish.
9. The method for preparing a water and rot proof finish according to claim 8, characterized in that, The screen for sieving the first component pre-product is 150 mesh; and the screen for sieving the second component pre-product is 200 mesh.
10. The method of preparing a water and rot proof finish according to claim 8, characterized in that, The temperature in the second stirring tank is controlled at 25-40 ℃ by means of cooling water through the jacket.
Citation Information
Patent Citations
Waterborne fluorocarbon modified acrylic polyurethane topcoat and preparation method thereof
CN108165151A